1996
DOI: 10.1021/bi952723e
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Position 52 in ERK2 Creates a Nonproductive Binding Mode for Adenosine 5‘-Triphosphate,

Abstract: Among the protein kinases, an absolutely conserved lysine in subdomain II is required for high catalytic activity. This lysine is known to interact with the substrate ATP, but otherwise its role is not well understood. We have used biochemical and structural methods to investigate the function of this lysine (K52) in phosphoryl transfer reactions catalyzed by the MAP kinase ERK2. The kinetic properties of activated wild-type ERK2 and K52 mutants were examined using the oncoprotein TAL2, myelin basic protein, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 40 publications
10
123
0
1
Order By: Relevance
“…This lysine is conserved in most kinases where it interacts with the α and β phosphates of ATP. Mutants of this lysine in other kinases, including lck (42), erk2 (41) and PKA (54), are also capable of binding ATP but are catalytically impaired. In PKR, the K296R mutation decreases adenosine nucleotide K d values by 3-6 fold but, in erk2 the analogous lysine → arginine mutation slightly increases the K m for ATP, suggesting that the lysine -ATP interaction does not contribute strongly to the overall binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…This lysine is conserved in most kinases where it interacts with the α and β phosphates of ATP. Mutants of this lysine in other kinases, including lck (42), erk2 (41) and PKA (54), are also capable of binding ATP but are catalytically impaired. In PKR, the K296R mutation decreases adenosine nucleotide K d values by 3-6 fold but, in erk2 the analogous lysine → arginine mutation slightly increases the K m for ATP, suggesting that the lysine -ATP interaction does not contribute strongly to the overall binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared bisphosphorylated ERK2 with both the wild-type and the catalytically impaired K52R mutant ERK2 by in vitro phosphorylation with a constitutively active form of MEK1 (MEK1/ G7B) (9,27). We found that it was easier to achieve full phosphorylation stoichiometry with ERK2/K52R than with the wild-type ERK2, possibly because of the lower ATPase activity of the mutant (39). The homogeneity and phosphorylation stoichiometry of the bisphosphorylated ERK2 preparations were verified by SDS-PAGE and liquid chromatography-mass spectrometry as described previously (4,7,9).…”
Section: Effect Of Mutations In Heptp On Erk2 Dephosphorylation-to Gamentioning
confidence: 99%
“…O domínio C-terminal consiste principalmente de hélices-alfa, além de quatro fitas-beta curtas que contêm muitos dos resíduos envolvidos na catálise. 15,16 MAPK requerem fosforilação de resíduo de tirosina e treonina, ambas catalisadas por MEK (quinase ativadora da MAP quinase), para se tornarem ativas. 17 Como conseqüência, essas quinases são inativadas pelos três maiores grupos de fosfatases: todas as que removem fosfato de serina/treonina ou de tirosina e as fosfatases dualespecíficas, que removem fosfato de serina, treonina e tirosina.…”
Section: Mapk (Proteínas Quinases Ativadas Por Mitógenos)unclassified